KAJIAN EMPIRIS TEORI PASAR EFISIEN (EFFICIENT MARKET HYPOTHESIS) PADA BURSA EFEK INDONESIA - Andreas Kiky (STIE Wiyatamandala, 2018)
Efficient Market Hypothesis (EMH) has been used by many academic professions as fundamental theory in financial literature for almost five decades. This theory creates basic understanding about how the information could affect volatility of stock price. Base on this theory, market is divided into 3 categories: weak; semi-strong and strong. Each of the market type represents information absorbtion in the stock price. On the strong market all available information (private or public) have been absorbed in stock price. On the semi-strong and weak market, information absorbtion is not fully reflected in stock price. Then the result of this condition could cause some market anomaly or abnormal return. This research examines the effect of number of news on stock volatility in the first model. Then this research also examines the effect of stock relative performance to the market with the beta that generate from model 1. This approach and methodology is taken from Stefan (2014) research on EMH Theory. This research applies linear regressions on both models. For statistical confirmation F test and t tests is applied to confirm the research hypothesis. From both model this research also examines R2 value of model in order to check the goodness of fit from the model. Keyword : Efficient Market Hypothesis (EMH); Heuristic Bias; Linear Regression; Adaptive Market.